Science Teacher Education in Australia: Initiatives and Challenges to Improve the Quality of Teaching - Treagust, David; Won, Mihye; Petersen, J.; Wynne, G. (Springer, 2015)
In this article, we describe how teachers in the Australian school system are educated to teach science and the different qualifications that teachers need to enter the profession. The latest comparisons of Australian students in international science assessments have brought about various accountability measures to improve the quality of science teachers at all levels. We discuss the issues and implications of government initiatives in preservice and early career teacher education programs, such as the implementation of national science curriculum, the stricter entry requirements to teacher education programs, an alternative pathway to teaching and the measure of effectiveness of teacher education programs. The politicized discussion and initiatives to improve the quality of science teacher education in Australia are still unfolding as we write in 2014.